Blood and treasure : Daniel Boone and the Fight for America's First Frontier - Drury, Bob; Clavin, Thomas (New York : St. Martin's Press, 2021)
"The explosive true saga of the legendary figure, Daniel Boone, and the bloody struggle for America's frontier ... It is the mid-eighteenth century, and in the 13 colonies founded by Great Britain, anxious colonists desperate to conquer and settle North America's 'First Frontier' beyond the Appalachian Mountains engage in a never-ending series of bloody battles. These violent conflicts are waged against the Native American tribes whose lands they covet, The French, and finally against the mother country itself in an American Revolution destined to reverberate around the world. This is the setting of Blood and Treasure and the guide to this epic narrative is none other than America's first and arguably greatest pathfinder Daniel Boone--not the coonskin cap-wearing caricature of popular culture but the flesh-and-blood frontiersman and Revolutionary War hero whose explorations into the forested frontier beyond the great mountains would become the stuff of legend. Now, thanks to painstaking research by two award-winning authors, the story of the brutal birth of the United States is told through the eyes of both the ordinary and larger-than-life men and women, white and Native American, who witnessed it. This fast-paced and fiery narrative, fueled by contemporary diaries and journals, newspaper reports, and eyewitness accounts, is a stirring chronicle of the conflict over America's 'First Frontier' that places the reader at the center of this remarkable epoch and its gripping tales of courage and sacrifice"--
Includes bibliographical references (pages 369-372) and index.
Keywords: Boone, Daniel, -- 1734-1820; Pioneers -- Biography -- Kentucky; Explorers -- Biography -- Kentucky; Indians of North America -- Wars -- 1750-1815; Frontier and pioneer life -- Kentucky; Frontier and pioneer life -- United States; United States -- Biography -- History -- Revolution, 1775-1783; United States -- Territorial expansion; Biographies